Analisis Unsur Instrinsik Dan Nilai Moral Dalam Cerpen “Robohnya Surau Kami” Karya Ali Akbar Navis - Ulfiatussalwa Ulfiatussalwa; Syifa Nur Rohman (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The short story "Robohnya Surau Kami" by Ali Akbar Navis is a literary work that is rich in meaning and moral values. This research aims to analyze the intrinsic elements that make up this short story, including theme, characterization, plot, setting and language style, as well as exploring the moral values ​​contained in it. Through this analysis, it was found that the main theme of this short story is about social responsibility and egoism in society. The strong characterizations, especially those of Grandpa Garin and Ajo Sidi, depict the conflict between spiritual obligations and responsibility towards the family. A storyline that uses a backwards technique provides depth to the narrative, while settings depicting people's daily lives add relevant social context. The language style used by Navis, with figures of speech and cynicism, provides sharp criticism of people's behavior. The moral values ​​that can be taken from this short story include the importance of social awareness, balance between worship and responsibility, as well as criticism of selfish attitudes. Thus, this short story not only functions as entertainment, but also as a reflection for readers to reflect on attitudes and behavior in everyday life.